New monstersaur specimens from the Kaiparowits Formation of Utah reveal unexpected richness of large-bodied lizards in Late Cretaceous North America - C. Henrik Woolley; Joseph J. W. Sertich; Keegan M. Melstrom; Randall B. Irmis; Nathan D. Smith (Royal Society Open Science, 2025)
Monstersauria (Squamata, Anguimorpha) fossils are present in most Upper Cretaceous sedimentary basins in western North America, but despite almost a century of collection, their record remains extremely fragmentary. Here, we describe new material belonging to large-bodied monstersaurs, including a new taxon, Bolg amondol gen. et sp. nov., based on a fragmentary associated skeleton and co-occurring specimens from the middle unit of the upper Campanian Kaiparowits Formation of Grand Staircase–Escalante National Monument in southern Utah, USA. Phylogenetic analyses recover B. amondol within Monstersauria, with two unique anatomical features: fused osteoderms on the jugal and the presence of autotomy septa on the distal caudal vertebrae. Critically, B. amondol is morphologically distinct from the problematic Late Cretaceous North American monstersaur Palaeosaniwa canadensis, whereas co-occurring monstersaur vertebrae and parietals from the Kaiparowits Formation (cf. P. canadensis) highlight a pressing need for a reassessment of this important, widespread taxon. These results offer new evidence that at least three lineages of distinct, large-bodied monstersaurian lizard were present on the palaeolandmass of Laramidia during the Campanian Stage. Importantly, B. amondol represents the most complete squamate recovered from late Campanian southern Laramidia and reveals key anatomical characteristics for future identification of isolated lizard fossil elements.